Aesthetic appraisals of literary style and emotional intensity in narrative engagement are neurally dissociable - Franziska Hartung; Yuchao Wang; Marloes Mak; Roel Willems; Anjan Chatterjee (Communications Biology, 2021)
Hartung & Wang et al. use fMRI data from 52 participants to explore two aspects of aesthetic experiences during narrative engagement - literariness and narrative fluctuations in appraised emotional intensity. Their results demonstrate a neural dissociation in processing literary form and emotional content in stories and generate questions about the function of and interaction between attention, social cognition, and semantic systems during literary engagement.